The imaging diagnostic skill of physicians in Primary Health Care - Miguel Angel Amaró Garrido; Carmen Lydia Díaz Quintanilla; Tatiana Hernández González; Mirian Belkis Nápoles Valdés; Niurbys Mireya Morales Tamayo; Armando Enrique Rodríguez Expósito (Gaceta Médica Espirituana, 2024)
Background: Scientific progress demands the training of competent healthcare professionals so that their clinical and imaging skills become an essential and efficient component in Primary Health Care.